Kinesin-II is required for axonal transport of choline acetyltransferase in Drosophila. - Ray, K.; Perez, S.E.; Yang, Z.; Xu, J.; Ritchings, B.W.; Steller, H.; Goldstein, L.S. (Journal of Cell Biology, 1999)
KLP64D and KLP68D are members of the kinesin-II family of proteins in Drosophila. Immunostaining for KLP68D and ribonucleic acid in situ hybridization for KLP64D demonstrated their preferential expression in cholinergic neurons. KLP68D was also found to accumulate in cholinergic neurons in axonal obstructions caused by the loss of kinesin light chain. Mutations in the KLP64D gene cause uncoordinated sluggish movement and death, and reduce transport of choline acetyltransferase from cell bodies to the synapse. The inviability of KLP64D mutations can be rescued by expression of mammalian KIF3A. Together, these data suggest that kinesin-II is required for the axonal transport of a soluble enzyme, choline acetyltransferase, in a specific subset of neurons in Drosophila. Furthermore, the data lead to the conclusion that the cargo transport requirements of different classes of neurons may lead to upregulation of specific pathways of axonal transport.